Manajemen Pemasaran Pendidikan dalam Meningkatkan Kepercayaan Masyarakat terhadap Madrasah Tsanawiyah Syubbanul Wathon: Educational Marketing Management in Increasing Public Trust in Madrasah Tsanawiyah Syubbanul Wathon - Yusuf, Ahmad Ardi; Sholikhun, Muhamad; Wafirah, Milna (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Targeted marketing management at Madrasah Tsanawiyah Syubbanul Wathon has played a role in building and maintaining public trust, which then contributed to the increase in the number of registrants each year. Madrasah Tsanawiyah Syubbanul Wathon applies the marketing mix concept which includes product, price, place, promotion, process, physical evidence, and people to attract prospective students and build a positive image in the community. This study aims to analyze the effectiveness of the marketing management strategy implemented by Madrasah Tsanawiyah Syubbanul Wathon in increasing public trust. The research method used is descriptive qualitative, with data collection through interviews, observations, and documentation. The results of the study indicate that the marketing mix strategy implemented has succeeded in increasing the number of registrants significantly, from 290 registrants in 2019/2020 to 477 registrants in 2024/2025. Key success factors include the madrasah's flagship programs, competitive tuition fees, strategic location, effective promotion, responsive service, and adequate facilities. Students' academic and non-academic achievements also strengthen the positive image of the madrasah in the eyes of the community. The conclusion of this study is that the implementation of targeted and integrated educational marketing management through the marketing mix strategy (7P) can increase public trust and interest in enrolling in Madrasah Tsanawiyah Syubbanul Wathon.